A Juridical Review of the Disharmony Between Central and Regional Government Regulations Regarding Sailing Permit Authority: A View From Principles of Balance and Public Interest - Demson Tiopan; Shelly Kurniawan; Marsya Shalviera Amanda (Syntax Literate, 2023)
The practice of sailing permits encounters challenges when the issuance of relevant sailing permits does not align with the designated jurisdictional authorities, as shown in the case involving KM Karya Indah. This study aims to identify the underlying causes of disharmony between Central and Regional Government Regulations regarding jurisdictional authority over sailing permits. Additionally, the study seeks to establish the proper approach to managing sailing permits based on the principles of balance and public interest. The research employed a normative legal research method, utilizing both the Statute Approach and the Conceptual Approach. Primary and secondary legal sources were employed as research materials. The findings indicate that within the domain of jurisdictional authority related to sailing permits, there is a lack of congruence between Central and Regional Government Regulations. In particular, the regional regulations necessitate that the processing of sailing permits should occur through the respective region first, under the jurisdiction of the Governor as the responsible authority. However, the practical application deviates from this structure, as the sailing permit processing is directly pursued at the central government level, and endorsed by relevant parties. The issuance of the pertinent sailing permits should align with the designated jurisdiction and the respective authorizing entities to avoid disharmony among regulations. Such harmonization is necessary to maintain balance and uphold the public interest, which serves both the permit applicants and the broader society. Keywords: